Analisis Perencanaan Audit Laporan Keuangan Pada Kantor Akuntan Publik KURNIAWAN, KUSMADI, DAN MATHEUS - Hafifah Nasution; Lysa Nur Awalianti (Institut Bisnis dan Informatika Kesatuan, 2020)
This research was conducted in KAP Kurniawan, Kusmadi and Matheus, which aims to analyse the suitability of audit planning of financial statement by KAP Kurniawan, Kusmadi and Matheus with the audit planning of financial statement based on the Professional Standard of Public Accountant (SPAP). Research method that used is descriptive analysis with a qualitative approach and the type of data used is primary data and secondary data. Primary data is collected through interviews, while secondary data by collecting audit planning of financial statements documents in KAP Kurniawan, Kusmadi and Matheus. The results of this research show that the audit planning of financial statement by KAP Kurniawan, Kusmadi and Matheus in accordance with the audit planning of financial statement based on SPAP issued by Institute of Public Accountants of Indonesia (IAPI). The advice given to KAP Kurniawan, Kusmadi and Matheus is always implement audit plan in accordance with SPAP because a good audit planning will improve audit quality.